Broken Naira: A Study of the Impact of Exchange Rates Movement in Nigeria - Andrew Pinnock; Asim Majeed; Paul Bocij; Said Baadel (International Journal of Management and Data Analytics)
Multinational Corporations involved in international business operations are exposed to movement in the exchange rate. The purpose of this study is to identify the factors that are responsible for exchange rate movements and to assess the impact they have on such organizations using the Nigerian market as a case study. A quantitative research approach and a descriptive ex-post facto research strategy were adopted for this study. During a span of ten years, a sample of exporting and non-exporting sector companies listed in the Nigerian stock exchange are analyzed. The findings revealed that the manufacturing company showed a high level of sensitivity with the movement in the exchange rate to the returns from the firm compared to the non-manufacturing company, and the correlation analysis indicated the inflation and debt levels to be key factors. The results from the study have revealed a significant relationship between some systematic factors and exchange rate movement which can be useful to multinational corporations, government entities, and other key international business stakeholders in Nigeria.